Lysine and methionine in diets for Apis mellifera infested by mite Varroa jacobsoni - Couto, Regina Helena Nogueira; Neto, Manoel Garcia; Junqueira, Otto Mack (Pesquisa Agropecuaria Brasileira, 2014)
One experiment was conducted feeding bees (Apis mellifera) with corn-soybean meal basal diets with 40% crude protein (A) with the addition of methionine (B), lysine and (C) methionine plus lysine (D). The lowest feed intake was observed when the bees were fed the diet supplemented by soybean and ground corn with 40% of crude protein with the addition of methionine and lysine. The addition of these two aminoacids did not affect the behavior of collection when compared with the control group. It was observed that the egg-larvae area remained constant in the treatments A, C and D, and that the number of pupae was constant in spite of the decrease of this area. As for the level of infestation by Varroa jacobsoni.
Keywords: honeybee nutrition; mites corn-soybean meal (Zea mays - Glycine max)